2020
DOI: 10.5812/msnj.106312
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Consequences of Parents Having Child with Thalassemia: Qualitative Study

Abstract: Background: Thalassemia can affect different aspects of life the same as any other chronic disease. Despite therapeutic measures of thalassemia, the patient and families encounter several physical and psychological problems. Having a child with thalassemia can disrupts the family mental balance. Objectives: The purpose of this study is to explain the consequences of parents who have children with thalassemia. Methods: Inductive qualitative approach was applied in 2017 - 2018 in Hajar Hospital. Semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Basrah centre for hereditary blood diseases contain a large cohort of heterogenous blood disease that are all categorised as hereditary, from them sickle cell diseases followed by thalassemia syndromes have its predominancy, Most of the families are large size (5-7) in 70.5 %, the vast majority of mothers were non-employed while only 49.2 % of the fathers were employed, consanguinity marriage was evident in a (77.7%), most of the families (80.3%) involve less than 3 effected child, in correspondence to data from Nineveh study at 2018 same characteristics of family size, consanguinity marriage and parental education but higher percentage of non-employment in our cohort fathers, with a higher number of effected Childs in the families enrolled [11] . Family breakage or social breakage was not evident in (79.5%) which greatly lesser than another studies in Iran [10] but it close to Nineveh cohort in which 24.9% of the marriages were threatened by divorce [11] .…”
Section: Discussionmentioning
confidence: 78%
“…Basrah centre for hereditary blood diseases contain a large cohort of heterogenous blood disease that are all categorised as hereditary, from them sickle cell diseases followed by thalassemia syndromes have its predominancy, Most of the families are large size (5-7) in 70.5 %, the vast majority of mothers were non-employed while only 49.2 % of the fathers were employed, consanguinity marriage was evident in a (77.7%), most of the families (80.3%) involve less than 3 effected child, in correspondence to data from Nineveh study at 2018 same characteristics of family size, consanguinity marriage and parental education but higher percentage of non-employment in our cohort fathers, with a higher number of effected Childs in the families enrolled [11] . Family breakage or social breakage was not evident in (79.5%) which greatly lesser than another studies in Iran [10] but it close to Nineveh cohort in which 24.9% of the marriages were threatened by divorce [11] .…”
Section: Discussionmentioning
confidence: 78%
“…[ 27 ] Furthermore, the results of other studies by Pouraboli et al . [ 28 ] and Heidari and Ahmadi[ 29 ] revealed that difficulties of caring of thalassemia children consequently resulted in psychological tensions to their parents. Hence, efforts should be made to alleviate the suffering of mothers by providing appropriate psychological care facilities for mothers of children with thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, one of the most important challenges for the mothers was their physical distress. Other studies have reported that mothers experience a variety of physical problems such as fatigue, weakness, acute and chronic diseases ( 8 , 24 ). Dahnil et al, showed that thalassemic children's parents, especially mothers, suffered more from physical and social problems than their children and needed comprehensive support for caring for their children ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that mothers play an active role in caring for their children and spend much time with them ( 6 , 7 ). Moreover, in Iranian culture and society, mothers are assumed to have the most important role in caring for a sick child ( 7 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation